2023
DOI: 10.1039/d2nj05744a
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the electrochemical performance of ZnO nanomaterials through a conductive CuS matrix for aqueous supercapacitors

Abstract: The impressive electrochemical performance of metal oxides/metal sulfides and their derivatives are proven to be innovative electrodes for achieving a remarkable performance for supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…The capacitor uses a novel electrode with a vanadium pentoxide/zinc oxide (V 2 O 5 /ZnO) stacked structure and is optically responsive. Mubeen et al [70] reported novel ZnO/CuS composite materials with different CuS ratios used as the electrode materials for supercapacitor applications. The capacitive performances of ZnO/CuS electrodes were measured in a three-electrode cell, where a capacitance of 487 F g −1 , a high-power density of 13,448 W kg −1 , and a maximum energy density of 26 W h kg −1 were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The capacitor uses a novel electrode with a vanadium pentoxide/zinc oxide (V 2 O 5 /ZnO) stacked structure and is optically responsive. Mubeen et al [70] reported novel ZnO/CuS composite materials with different CuS ratios used as the electrode materials for supercapacitor applications. The capacitive performances of ZnO/CuS electrodes were measured in a three-electrode cell, where a capacitance of 487 F g −1 , a high-power density of 13,448 W kg −1 , and a maximum energy density of 26 W h kg −1 were achieved.…”
Section: Introductionmentioning
confidence: 99%